El proyecto educativo institucional en el desarrollo académico y administrativo de la unidad educativa fiscal “Adolfo Jurado González”, de la parroquia El Sagrario, cantón y provincia de Loja, en el período 2011 – 2012 - Vera Gómez, Nancy Victoria (2014)
The main objective of the present investigation is to determine the incidence of the Institutional Education Project with in the academic and administrative development from Adolfo Jurado González School belonging to the El Sagrario parish, from the canton and province of Loja, in the period 2011-2012.The investigative development was supported by the following methods: analytic, synthetic, inductive and deductive that served for the processing of empiric information, as well as the analysis of chaos establishing comparisons, relations and generalities in order to determine and recognize the causes of the problems or difficulties in the development of the PEI and its consequences in the academic and administrative growth of the institution. The technique applied in this investigation was the survey, the same that was designed and validated with general and specific questions to the educational community: administrators, teachers, students and parents. The survey with closed-ended questions was the instrument used in individually applied to the informants in order to obtain indirectly assessments. After the investigation it was concluded that the implementation of the PEI in the institution will be affected by the limited participation level as well as the lack of responsibility and involving from the participants as a result of not having work efficiently the diffusion and sensitization component reason why the PEI was not concluded. It could also be determined that the evaluation, control and tracing actions were not satisfactory accomplished in this institution. The results of the administrative improvement are shown discretely and do not constitute an effective evidence in the implementation of the PEI. It is conclude therefore the urgency of a training process as well as assessment about the implementation of the PEI in the institution subject of this investigation; recommending the implementation of a training and assessment suggestion involving the entire school community in order to redefine the PEI. This recommendation was considered to create an alternative suggestion that was implemented in the institution in order to redefine the construction of PEI with a highly participation approach.